The rural practicum : preparing a quality teacher workforce for rural and regional Australia - J Kline; S White; G Lock (2013)
Communities play a critical role in supporting pre-service teachers during rural and regional professional experience. This support, coupled with access to teacher educators and university resources, appears to positively influence graduate attitudes toward taking up a rural appointment. These are among the key findings to emerge from open-ended responses within 263 surveys completed for the Rethinking Teacher Education for Rural and Regional Sustainability—Renewing Teacher Education for Rural and Regional Australia project (TERRAnova). The national surveys, collected annually from 2008-2010, monitored the impact of state-based financial incentives designed to promote rural and regional professional experience. Findings discussed in this article have implications for teacher educators and rural school leaders as they work in partnership with communities to support pre-service teachers on rural and regional practicum.